SnO2 / expanded graphite composite material as well as preparation method and application thereof

The preparation of SnO2/expanded graphite composite material through microwave heating solves the problem of low specific capacity of expanded graphite/tin oxide composite material, achieves high specific capacity and good cycling performance, and improves the electrochemical performance of sodium ion batteries.

CN120553699APending Publication Date: 2025-08-29ZHENGZHOU ZHONGKE EMERGING IND TECH RES INST +1

Patent Information

Application Number
CN202510700131.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-28
Publication Date
2025-08-29

AI Technical Summary

Technical Problem

The existing expanded graphite/tin oxide composites have low specific capacity and poor low conductivity and cycling performance of SnO2, which limits the electrochemical performance of sodium ion batteries.

Method used

The SnO2/expanded graphite composite was prepared by microwave heating. By generating nano SnO2 in situ between graphite layers, the sodium storage advantages of metal oxides and expanded graphite were synergistically exerted to improve electrochemical performance.

Benefits of technology

The prepared SnO2/expanded graphite composite material has high specific capacity and good cycle stability. The discharge specific capacity in the first week reaches 1734.5mAh/g, the Coulon efficiency in the first week reaches 96.3%, and the capacity retention rate after 700 weeks is above 95%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120553699A_ABST
    Figure CN120553699A_ABST
Patent Text Reader

Abstract

The invention provides a SnO2 / expanded graphite composite material as well as a preparation method and application thereof, belongs to the technical field of sodium ion batteries, and aims to solve the technical problems of low specific capacity of expanded graphite and unstable SnO2 cycle performance. The preparation method of the SnO2 / expanded graphite composite material comprises the following steps: (1) mixing expandable graphite, soluble tin salt and a solvent to obtain a mixed solution; (2) evaporating the mixed solution to dryness to obtain a graphite intercalation compound; and (3) carrying out microwave heating on the graphite intercalation compound to obtain the SnO2 / expanded graphite composite material. The SnO2 / expanded graphite composite material prepared by the invention is used as a sodium-ion battery negative electrode material, can effectively overcome the defect of poor capacity when a carbon material is independently used and the defects of low conductivity and poor cycle performance when SnO2 is independently used, can synergistically exert the sodium storage advantages of the metal oxide and the expanded graphite, makes up the respective defects, and can be used for preparing the sodium-ion battery negative electrode material. Therefore, the electrochemical performance of the sodium-ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a SnO2 / expanded graphite composite material and a preparation method and application thereof. Background Art

[0002] With the large-scale application of lithium-ion batteries in electronics, electric vehicles, grid energy storage, and other fields, a series of problems caused by the shortage and rapid consumption of lithium resources have received widespread attention. Sodium-ion batteries have similar working mechanisms and battery structures to lithium-ion batteries and are compatible with lithium-ion battery production lines. Sodium resources are abundant and widely distributed. Sodium-ion batteries are low-cost, safe, and have excellent high- and low-temperature performance. They are the most competitive alternative to lithium-ion batteries in large-scale energy storage and low-speed electric vehicles. Due to the large radius of sodium ions, it is difficult for them to embed into the closely spaced graphite interlayers to form stable compounds. Therefore, sodium-ion battery anode materials cannot directly use the commercialized graphite anode materials of lithium-ion batteries. Therefore, the development of suitable sodium-ion battery anode materials is crucial.

[0003] Among the numerous sodium-ion battery anode materials, carbon-based materials, metal oxides, metal sulfides, alloys, non-metallic elements, and organic materials have been widely studied. For example, SnO2 has a theoretical sodium storage capacity of up to 1378 mAh / g, but its volume expansion and low conductivity restrict its widespread application. Expanded graphite (EG), a graphite-derived material, retains the long-range ordered layered structure of graphite. Through manipulation, a larger interlayer spacing can be achieved, resulting in excellent sodium storage performance and cycling stability. However, its specific sodium storage capacity is relatively low, generally not exceeding 300 mAh / g. Patent Publication No. CN 116573639A discloses a method for preparing a sodium-ion battery anode material using a liquid-phase reaction by embedding expanded graphite with selenide. Transition metal selenides are prepared by coprecipitation and embedded in the expanded graphite using concentrated sulfuric acid co-heating. However, the specific capacity of the prepared expanded graphite embedded with selenide is low, and the specific capacity improvement compared to pure expanded graphite is relatively small. Patent publication number CN107910522A discloses the synthesis of an expanded graphite-tin oxide composite material and its application in lithium-ion batteries. This patent uses a hydrothermal reaction to intercalate tin dioxide microspheres into graphite to produce an expanded graphite / tin oxide composite material. However, the SnO2 size and graphite interlayer spacing are difficult to control in the hydrothermal method, and the specific capacity of the prepared expanded graphite / tin oxide composite material is lower than that of pure tin oxide material. Summary of the Invention

[0004] To address the technical problem of low specific capacity of expanded graphite / tin oxide composite materials, the present invention proposes a SnO2 / expanded graphite composite material, its preparation method and application, and utilizes microwave heating to achieve in-situ symbiotic construction of the SnO2 / expanded graphite composite material. This can synergistically leverage the sodium storage advantages of metal oxides and expanded graphite, making up for their respective deficiencies, thereby improving the electrochemical performance of sodium-ion batteries.

[0005] In order to achieve the above object, the technical solution of the present invention is achieved as follows:

[0006] A SnO2 / expanded graphite composite material, the preparation method comprising the following steps:

[0007] (1) mixing expandable graphite, a soluble tin salt and a solvent to obtain a mixed solution;

[0008] (2) evaporating the mixed solution to dryness to obtain a graphite intercalation compound;

[0009] (3) heating the graphite intercalation compound with microwaves to obtain a SnO2 / expanded graphite composite material;

[0010] The preparation method of the expandable graphite comprises the following steps: adding flake graphite and an oxidant into a strong acid solution, stirring, filtering, washing and drying.

[0011] The oxidant is potassium dichromate, sodium nitrate or potassium perchlorate, and the strong acid solution is sulfuric acid or nitric acid; the concentration of sulfuric acid is 60-98% (mass percentage concentration), and the concentration of nitric acid is 65-68% (mass percentage concentration).

[0012] The mass ratio of the flake graphite to the oxidant is 1:(0.2-2.3), and the mass volume ratio of the flake graphite to the strong acid solution is 1:(5-20) g / ml.

[0013] The soluble tin salt is tin chloride, preferably, the tin chloride is tin chloride pentahydrate; the solvent is deionized water.

[0014] In the step (1), a soluble tin salt is first dissolved to prepare a tin salt solution, and then expandable graphite is added to the tin salt solution.

[0015] The concentration of the tin salt solution is 0.1-80 g / L, and the mass volume ratio of the expandable graphite to the tin salt solution is 1:(15-120) g / mL.

[0016] The mixed solution in step (1) is shaken on a shaker for 10 min-5 h and then evaporated to dryness; the evaporation is performed using a rotary evaporator at a rotation speed of 50-200 rpm.

[0017] The power of the microwave heating is 500-3000W, and the reaction time is 20s-2min.

[0018] The invention discloses an application of a SnO2 / expanded graphite composite material in a sodium ion battery, wherein the SnO2 / expanded graphite composite material is used as a negative electrode material.

[0019] Beneficial effects of the present invention:

[0020] (1) The present technical solution prepares SnO2 / expanded graphite composite materials for use as negative electrode materials for sodium ion batteries, which can effectively make up for the shortcomings of poor capacity when using carbon materials alone, as well as the shortcomings of low conductivity and poor cycle performance when using SnO2 alone. It can synergistically exert the sodium storage advantages of metal oxides and expanded graphite to make up for their respective shortcomings, thereby improving the electrochemical performance of sodium ion batteries.

[0021] (2) This technical solution utilizes the intercalation properties of graphite. Soluble SnCl₄ molecules are inserted into the graphite intercalation compound in solution through shaking and oscillation. After evaporation, instant microwave heating is performed to generate expanded graphite. Simultaneously, the SnCl₄ is converted to SnO₂, achieving the in-situ symbiotic construction of a SnO₂ / expanded graphite composite material, enabling the preparation of high-performance composite materials. The SnO₂ / expanded graphite composite material has a moderate tap density, resolving the issue of expanded graphite's low tap density and poor processing properties as a negative electrode material.

[0022] (3) The size of SnO2 generated by instantaneous microwave heating is reduced to the nanoscale, which can slow down its volume expansion and improve its electrochemical performance. The generation of nano-SnO2 between the expanded graphite layers can increase the distance between the graphite layers, which is conducive to the intercalation and storage of sodium ions. The prepared SnO2 / expanded graphite composite material has extremely high specific capacity and first-cycle coulombic efficiency. The first-cycle discharge specific capacity reaches 1734.5mAh / g, the first-cycle coulombic efficiency reaches 96.3%, the reversible specific capacity reaches 1670.8mAh / g, and the capacity retention rate after 700 cycles is above 95%. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0024] Figure 1 XRD patterns of the raw material SnCl4·5H2O, SnO2 in Comparative Example 1, and SnO2 / EG in Example 1.

[0025] Figure 2 This is the SEM image of SnO2 in Comparative Example 1.

[0026] Figure 3 This is the EDS element distribution diagram of SnO2 in Comparative Example 1, (a) is the Sn element, and (b) is the O element.

[0027] Figure 4 This is the SEM image of SnO2 / EG in Example 1

[0028] Figure 5 This is the EDS element distribution diagram of SnO2 / EG in Example 1, (a) is the C element, (b) is the Sn element, and (c) is the O element.

[0029] Figure 6 This is the first week charge and discharge curve of SnO2 in Comparative Example 1 and SnO2 / EG in Example 1 used as negative electrode materials for sodium ion batteries.

[0030] Figure 7 The figure shows the rate performance curves of SnO2 in comparative example 1 and SnO2 / EG in example 1 when used as negative electrode materials for sodium ion batteries at different current densities.

[0031] Figure 8 The graph shows the cycle performance curves of SnO2 in Comparative Example 1 and SnO2 / EG in Example 1 used as negative electrode materials for sodium ion batteries. DETAILED DESCRIPTION

[0032] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] A SnO2 / expanded graphite composite material, the preparation method comprising the following steps:

[0035] Place 10g of flake graphite in a beaker, add 50ml of 60% sulfuric acid solution (mass percentage concentration), stir in a 40°C water bath for 10min, gradually add 2g of potassium dichromate solid, stir in a 40°C water bath for 90min, filter and collect the precipitate, wash the precipitate to a pH of 6-7, and dry the precipitate to obtain expandable graphite.

[0036] 1g of expandable graphite was poured into 100mL of 1g / L SnCl4 solution and shaken on a shaker at 100rpm for 120min. The water was then evaporated to dryness using a rotary evaporator at 50rpm to obtain a graphite intercalation compound. This was then placed in a microwave muffle furnace and heated for 2min at 1000W to produce a SnO2 / EG composite.

[0037] The SnO2 / EG composite material, CMC binder and SP conductive agent were weighed according to the mass ratio of active material: CMC: SP = 90:5:5, poured into an agate ball mill, and deionized water was added according to the solid content standard of 25%. The mixture was ball milled at 600r / min for 30min to obtain a uniform black slurry, which was coated on an aluminum foil current collector to make a negative electrode sheet and assembled into a sodium ion battery.

[0038] Example 2

[0039] A SnO2 / expanded graphite composite material, the preparation method comprising the following steps:

[0040] Put 10g of flake graphite into a beaker, add 100ml of 70% sulfuric acid solution, stir in a 40℃ water bath for 10min, gradually add 3g of sodium nitrate solid, stir in a 40℃ water bath for 120min, filter and collect the precipitate, wash the precipitate to a pH value of 6-7, and dry the precipitate to obtain expandable graphite.

[0041] 1g of expandable graphite was poured into 15mL of 1g / L SnCl4 solution and shaken on a shaker at 50rpm for 20min. The water was then evaporated to dryness using a rotary evaporator at 70rpm to obtain a graphite intercalation compound. This was then placed in a microwave muffle furnace and heated for 1min at 2000W to produce a SnO2 / EG composite.

[0042] The SnO2 / EG composite material, CMC binder and SP conductive agent were weighed according to the mass ratio of active material: CMC: SP = 90:5:5, poured into an agate ball mill, and deionized water was added according to the solid content standard of 25%. The mixture was ball milled at 600r / min for 30min to obtain a uniform black slurry, which was coated on an aluminum foil current collector to make a negative electrode sheet and assembled into a sodium ion battery.

[0043] Example 3

[0044] A SnO2 / expanded graphite composite material, the preparation method comprising the following steps:

[0045] Put 10g of flake graphite into a beaker, add 150ml of 98% sulfuric acid solution, stir in a 40℃ water bath for 10min, gradually add 10g of potassium dichromate solid, stir in a 40℃ water bath for 90min, filter and collect the precipitate, wash the precipitate to a pH of 6-7, and dry the precipitate to obtain expandable graphite.

[0046] 1g of expandable graphite was poured into 30mL of 20g / L SnCl₄ solution and shaken on a shaker at 150rpm for 100min. The water was then evaporated to dryness using a rotary evaporator at 200rpm to obtain a graphite intercalation compound. This was then placed in a microwave muffle furnace and heated for 1min at 500W to produce a SnO₂ / EG composite.

[0047] The SnO2 / EG composite material, CMC binder and SP conductive agent were weighed according to the mass ratio of active material: CMC: SP = 90:5:5, poured into an agate ball mill, and deionized water was added according to the solid content standard of 25%. The mixture was ball milled at 600r / min for 30min to obtain a uniform black slurry, which was coated on an aluminum foil current collector to make a negative electrode sheet and assembled into a sodium ion battery.

[0048] Example 4

[0049] A SnO2 / expanded graphite composite material, the preparation method comprising the following steps:

[0050] Put 10g of flake graphite into a beaker, add 200ml of 90% sulfuric acid solution, stir in a 40℃ water bath for 10min, gradually add 23g of potassium dichromate solid, stir in a 40℃ water bath for 90min, filter and collect the precipitate, wash the precipitate to a pH of 6-7, and dry the precipitate to obtain expandable graphite.

[0051] 1g of expandable graphite was poured into 90mL of 50g / L SnCl₄ solution and shaken on a shaker for 200min at 300rpm. The water was then evaporated to dryness using a rotary evaporator at 150rpm to obtain a graphite intercalation compound. This was then placed in a microwave muffle furnace and heated for 20s at 3000W to produce a SnO₂ / EG composite.

[0052] The SnO2 / EG composite material, CMC binder and SP conductive agent were weighed according to the mass ratio of active material: CMC: SP = 90:5:5, poured into an agate ball mill, and deionized water was added according to the solid content standard of 25%. The mixture was ball milled at 600r / min for 30min to obtain a uniform black slurry, which was coated on an aluminum foil current collector to make a negative electrode sheet and assembled into a sodium ion battery.

[0053] Example 5

[0054] A SnO2 / expanded graphite composite material, the preparation method comprising the following steps:

[0055] Put 10g of flake graphite into a beaker, add 50ml of 65% nitric acid solution, stir in a 40℃ water bath for 10min, gradually add 11g of potassium dichromate solid, stir in a 40℃ water bath for 90min, filter and collect the precipitate, wash the precipitate to a pH of 6-7, and dry the precipitate to obtain expandable graphite.

[0056] 1g of expandable graphite was poured into 120mL of 80g / L SnCl₄ solution and shaken on a shaker at 100rpm for 120min. The water was then evaporated to dryness using a rotary evaporator at 50rpm to obtain a graphite intercalation compound. This was then placed in a microwave muffle furnace and heated for 2min at 1000W to produce a SnO₂ / EG composite.

[0057] The SnO2 / EG composite material, CMC binder and SP conductive agent were weighed according to the mass ratio of active material: CMC: SP = 90:5:5, poured into an agate ball mill, and deionized water was added according to the solid content standard of 20%. The mixture was ball milled at 600r / min for 30min to obtain a uniform black slurry, which was coated on an aluminum foil current collector to make a negative electrode sheet and assembled into a sodium ion battery.

[0058] Example 6

[0059] A SnO2 / expanded graphite composite material, the preparation method comprising the following steps:

[0060] Put 10g of flake graphite into a beaker, add 50ml of 68% nitric acid solution, stir in a 40℃ water bath for 10min, gradually add 10g of potassium perchlorate solid, stir in a 40℃ water bath for 90min, filter and collect the precipitate, wash the precipitate to a pH of 6-7, and dry the precipitate to obtain expandable graphite.

[0061] 1g of expandable graphite was poured into 120mL of SnCl₄ solution (0.1g / L) and shaken on a shaker at 100rpm for 120min. The water was then evaporated to dryness using a rotary evaporator at 50rpm to obtain a graphite intercalation compound. This was then placed in a microwave muffle furnace and heated for 2min at 500W to produce a SnO₂ / EG composite.

[0062] The SnO2 / EG composite material, CMC binder and SP conductive agent were weighed according to the mass ratio of active material: CMC: SP = 90:5:5, poured into an agate ball mill, and deionized water was added according to the solid content standard of 20%. The mixture was ball milled at 600r / min for 30min to obtain a uniform black slurry, which was coated on an aluminum foil current collector to make a negative electrode sheet and assembled into a sodium ion battery.

[0063] Comparative Example 1

[0064] 0.5 g of SnCl4·5H2O solid was placed in a microwave muffle furnace and heated in a microwave oven for 2 min at a microwave power of 1000 W to obtain SnO2.

[0065] SnO2, CMC binder and SP conductive agent were weighed according to the mass ratio of active material: CMC: SP = 90:5:5, poured into an agate ball mill, deionized water was added according to the solid content standard of 20-30%, and ball milled at 600r / min for 30 minutes to obtain a uniform black slurry, which was coated on an aluminum foil current collector to make a negative electrode sheet and assembled into a sodium ion battery.

[0066] Figure 1 The XRD patterns show that microwave heating of the SnCl4·5H2O solid yields a pure SnO2 phase. Characteristic peaks for SnO2 and SnO2 / EG appear at 2θ = 26°, 34°, 38°, and 52°, representing the 110, 101, 200, and 211 faces of SnO2, respectively. The peak intensity at 26° in the SnO2 / EG composite is greater than the other characteristic peaks due to the overlap of the strongest peaks of SnO2 and EG at this location. As can be seen from the figure, neither SnO2 nor SnO2 / EG exhibits characteristic peaks of SnCl4, indicating that microwave heating of the SnCl4·5H2O solid completely converts it into a pure SnO2 phase. The resulting material exhibits a single crystalline phase with sharp diffraction peaks, indicating good crystallinity and a stable structure.

[0067] Figure 2 The SEM image of SnO2 in Comparative Example 1 shows that the SnO2 generated after microwave heating of SnCl4·5H2O solid is small in size, nanometer scale, and agglomerates seriously. Figure 3 The EDS element distribution map confirmed the presence of Sn and O elements in the material.

[0068] Figure 4 The SEM image of SnO2 / EG in Example 1 shows the morphology of the SnO2 / EG composite material innovatively prepared by this technical solution. The SnO2 is small in size, nanometer scale, and evenly distributed on the graphite sheet without obvious agglomeration. Figure 5 The EDS element distribution map confirmed the presence of C, Sn and O elements in the material.

[0069] Figure 6The first week charge and discharge curves of SnO2 in Comparative Example 1 and SnO2 / EG in Example 1 as negative electrode materials for sodium ion batteries are shown. The charge and discharge voltage range is 0.0-2.0V, the current density is 30mA / g, the SnO2 discharge specific capacity is 812.2mAh / g, and the charge specific capacity is 835.4mAh / g. The SnO2 / EG composite material has a discharge specific capacity of 1734.5mAh / g and a charge specific capacity of 1670.8mAh / g. The SnO2 / EG composite material has an extremely high charge and discharge specific capacity, demonstrating the superiority of the material preparation method of this technical solution.

[0070] Figure 7 The figure shows the rate performance curves of SnO2 in the comparative example and SnO2 / EG in Example 1 as the negative electrode material for sodium ion batteries at different current densities. The charge and discharge voltage range is 0.0-2.0V. At current densities of 30mA / g, 50mA / g, 100mA / g, 200mA / g, 400mA / g, 800mA / g, and 1000mA / g, the reversible specific capacities of SnO2 are 793mAh / g, 456mAh / g, 302mAh / g, 170mAh / g, 98mAh / g, 65mAh / g, and 43mAh / g, respectively. The reversible specific capacities of SnO2 / EG are 1726mAh / g, 1329mAh / g, 788mAh / g, 729mAh / g, 498mAh / g, 380mAh / g, and 281mAh / g, respectively. The SnO2 / EG composite material has good rate performance, which is attributed to the fact that the technical solution generates nanoparticle SnO2, which has a short ion diffusion path during charging and discharging, and the composite with EG greatly improves the electronic conductivity, so the material is capable of large current charging and discharging.

[0071] Figure 8 The following are the cycle performance curves of SnO2 in Comparative Example 1 and SnO2 / EG in Example 1 used as negative electrode materials for sodium ion batteries. In the charge and discharge voltage range of 0.0-2.0V, at a current density of 100mA / g, the specific capacity of SnO2 gradually decays, while the specific capacity of SnO2 / EG remains stable. After 700 cycles, the specific capacity of SnO2 decays to 4% of the initial capacity, and the capacity retention rate of SnO2 / EG is above 95%. The SnO2 / EG composite material of this technical solution effectively compensates for the poor capacity of carbon materials used alone, as well as the low conductivity and poor cycle performance of SnO2 used alone. It synergistically leverages the sodium storage advantages of metal oxides and expanded graphite to compensate for their respective shortcomings, thereby greatly improving the electrochemical performance of sodium ion batteries.

[0072] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a SnO2 / expanded graphite composite material, characterized in that: The following steps are involved: (1) mixing expandable graphite, a soluble tin salt and a solvent to obtain a mixed solution; (2) evaporating the mixed solution to dryness to obtain a graphite intercalation compound; (3) The graphite intercalation compound is subjected to microwave heating to obtain a SnO2 / expanded graphite composite material.

2. The method for preparing the SnO2 / expanded graphite composite material according to claim 1, wherein The preparation method of the expandable graphite comprises the following steps: adding flake graphite and an oxidant into a strong acid solution, stirring, filtering, washing and drying.

3. The method for preparing the SnO2 / expanded graphite composite material according to claim 2, wherein The oxidant is potassium dichromate, sodium nitrate or potassium perchlorate, and the strong acid solution is sulfuric acid or nitric acid.

4. The method for preparing the SnO2 / expanded graphite composite material according to claim 3, wherein The mass ratio of the flake graphite to the oxidant is 1:(0.2-2.3), and the mass volume ratio of the flake graphite to the strong acid solution is 1:(5-20) g / ml.

5. The method for preparing the SnO2 / expanded graphite composite material according to any one of claims 1 to 4, characterized in that: The soluble tin salt is tin chloride, and the solvent is deionized water.

6. The method for preparing the SnO2 / expanded graphite composite material according to claim 5, wherein In the step (1), a soluble tin salt is first dissolved to prepare a tin salt solution, and then expandable graphite is added to the tin salt solution.

7. The method for preparing the SnO2 / expanded graphite composite material according to claim 6, wherein: The concentration of the tin salt solution is 0.1-80 g / L, and the mass volume ratio of the expandable graphite to the tin salt solution is 1:(15-120) g / mL.

8. The method for preparing the SnO2 / expanded graphite composite material according to claim 1, wherein The power of the microwave heating is 500-3000W, and the reaction time is 20s-2min.

9. A SnO2 / expanded graphite composite material prepared according to the method according to any one of claims 1 to 8.

10. Use of the SnO2 / expanded graphite composite material according to claim 9 in sodium ion batteries.

Citation Information

Patent Citations

  • Synthesis of expanded graphite-tin oxide composite material and application of expanded graphite-tin oxide composite material in lithium ion battery

    CN107910522A

  • Preparation method of expanded graphite inlaid selenide negative electrode material for sodium ion battery

    CN116573639A

Cited By

  • Battery monomer and preparation method thereof, battery device, power utilization device and energy storage device

    CN122315016A